Democracia na era da biopolítica e do biopoder: questão em análise - Marques, Wilson de Azevedo (2016)
The objective of the research, giving rise to this effort, seeks to address the problem of democracy in the age of biopower and of biopolitics and questions about making a living. There are at work, the issue of totalitarian behavior in the democratic process as a way to govern. The research method used by research takes the theoretical writings of the philosophers Hannah Arendt, Michel Foucault and Giorgio Agamben. I turn to other thinkers and other propositions that contribute to the importance of ethics and justice in public policy within, strengthening the idea of a humanistic policy as contributing to an orderly society. In current times, the power and its effect supersedes any and all interest when people move from their countries in search of legal and political security in the pursuit of biopolitics. Analyzes are rescues who warn us about this issues, aiming to avoid the trivialization of evil and power, preventing the dimensions of state power within a community, ends up preventing satisfactory social directions when it should be at the service of the order and protection, allowing the constitutional effectiveness. A change in the paradigm of language between the existing power relations and policy make live and let die is essential point along the social spheres, enabling the effectiveness of justice and biopolitics